Analysis of LPG, electric and induction cookers during cooking typical Ecuadorian dishes into the national efficient cooking program. (February 2016) - Martínez-Gómez, J.; Ibarra, D.; Villacis, S.; Cuji, P.; Cruz, P.R.
Highlights: Dishes have been cooked to analyze costs, time and energy consumption during cooking. An assessment of the effect of exhaust hood during Ecuadorian cooking. Parameters were measured during cooking mode, and idle mode. It has been compared organoleptic measurements in LPG and induction stoves. It has been analyzed by physicochemical and microbiological measurements. Abstract: This research aims to analyze cooking parameters in liquefied petroleum gas (LPG), electric resistance and induction stoves for eight dishes of the Ecuadorian cuisine. During tests, it has been monitored the temperature, time, electrical grid parameters, concentrations of CO and CO2 . In addition it has been studied the microbiological and physiochemical changes produced by the thermal treatment in food and a discriminative triangular test for determining the differences in the consumers perception between samples made with induction and LPG based stoves. The results showed which even with an exhaust hood working, there was still a significant value of concentration of CO and CO2 during cooking with a LPG stoves. As a result of these analyses the induction stove shows a better response during the heating process and energy efficiency which have influence in temperatures, taste, vitamin preservation, cooking times, energy consumption and cost to the user.